Analysis of scientific production about fetal alcoholic syndrome and their relationship with the health of children (Research, Society and Development, 2020)
An integrative review aimed at identifying what the scientific literature has approached about fetal alcohol syndrome and its relation with the health of the carrier child. The research was performed through the access to the Virtual Health Library, using the descriptors "fetal alcohol syndrome", "alcohol" and "child", between 2007 and 2017, the search resulted in the selection of eight articles that were Submitted to the Thematic Content Analysis Technique, giving rise to three descriptive categories. It was evidenced that the theme, despite the importance, is little clarified for women and health professionals, especially regarding the consequences of alcohol consumption during pregnancy. The health services have the duty to guide and direct the candidates for a preventive practice, through educational programs and correct approach. There is a need for training of professionals, so that strategies are developed in order to make pregnant women aware of the risks associated with alcohol use.